In vitro antimicrobial activity of S-649266, a catechol-substituted siderophore cephalosporin, when tested against non-fermenting Gram-negative bacteria. (7th December 2015) - Ito, Akinobu; Kohira, Naoki; Bouchillon, Samuel K.; West, Joshua; Rittenhouse, Stephen; Sader, Helio S.; Rhomberg, Paul R.; Jones, Ronald N.; Yoshizawa, Hidenori; Nakamura, Rio; Tsuji, Masakatsu; Yamano, Yoshinori
Abstract: Objectives: S-649266 is a parenteral siderophore cephalosporin antibiotic with a catechol moiety on its side chain. The in vitro antimicrobial activity of S-649266 against non-fermenting Gram-negative bacteria was evaluated and compared with the activities of meropenem, levofloxacin, cefepime, ceftazidime and piperacillin/tazobactam. Methods: MIC values of S-649266 were determined in Mueller–Hinton broth or Iso-Sensitest broth supplemented with apo-transferrin. Results: S-649266 showed potent in vitro activity against the non-fermenting Gram-negative bacteria Acinetobacter baumannii, Pseudomonas aeruginosa and Stenotrophomonas maltophilia, including MDR strains such as carbapenem-resistant A. baumannii and metallo-β-lactamase-producing P. aeruginosa . MIC90 s of S-649266 for A. baumannii, P. aeruginosa and S. maltophilia were 2, 1 and 0.5 mg/L, respectively, whereas MIC90 s of meropenem were >16 mg/L. S-649266 showed potent in vitro activities against A. baumannii producing carbapenemases such as OXA-type β-lactamases, and P. aeruginosa producing metallo-β-lactamases such as IMP type and VIM type. MIC90 values for these A. baumannii strains and P. aeruginosa strains were 8 and 4 mg/L, respectively. Conclusions: S-649266 is a novel antibiotic with potent in vitro activity against a range of non-fermenting Gram-negative bacteria, including MDR strains.